PENGEMBANGAN INSTRUMEN TES UNTUK MENGUNGKAP SUMBER MISKONSEPSI BERDASARKAN REPRESENTASI VISUAL DALAM SEGITIGA - Ita Sartika; Mohamad Rifat; Ahmad Yani T (Universitas Tanjungpura, 2021)
AbstractThis research aims to develop a test instrument to reveal sources of misconceptions based on visual representations so to produce instrument indicators of misconception on the concept of the base and height of the triangle. Testing of these instruments was carried out at SMAN 3 Teluk Keramat. This research is in the form of development research, with development procedures referring to the development of test instruments proposed by Djemari Mardapi, consisting of eight steps, namely: designing test instruments, developing test instruments, examining test instruments (validating test instruments), conducting test trials, analyzing test items, improve the test (revision), carry out the test (field trials) and interpretation the test results. Based on the analysis of the misconception test items, the misconception indicator was obtained in drawing the base and height of the triangle with various variations of the visual representation of the triangle and the misconception in determining the base of the triangle from the combination of triangular shapes.Keywords: Develop a Test Instrument, Sources of Misconceptions, The Base and Height of the Triangle, Visual Representations